New Directions in Assessing Performance Potential of Individuals and Groups : Workshop Summary - Pool, Robert, 1955- (National Academies Press, 2013)
As an all-volunteer service accepting applications from nearly 400,000 potential recruits annually from across the U.S. population, the U.S. military must accurately and efficiently assess the individual capability of each recruit for the purposes of selection, job classification, and unit assignment. New Directions for Assessing Performance Potential of Individuals and Groups is the summary of a workshop held April 3-4, 2013 to examine the future of military entrance assessments. This workshop was a part of the first phase of a larger study that will investigate cutting-edge research into the measurement of both individual capabilities and group composition in order to identify future research directions that may lead to improved assessment and selection of enlisted personnel for the U.S. Army. The workshop brought together scientists from a variety of relevant areas to focus on cognitive and noncognitive attributes that can be used in the initial testing and assignment of enlisted personnel. This report discusses the evolving goals of candidate testing, emerging constructs and theory, and ethical implications of testing methods.